[tex](\sqrt3-1)x-3=2x(\sqrt3+1)-3\sqrt3\\
(\sqrt3-1)x-3+3\sqrt3=2x(\sqrt3+1)\\
(\sqrt3-1)x+3(\sqrt3-1)=2x(\sqrt3+1)\\
(\sqrt3-1)(x+3)=2x(\sqrt3+1)\\
\frac{x+3}{2x}=\frac{\sqrt3+1}{\sqrt3-1}\\
\frac{x+3}{2x}=\frac{(\sqrt3+1)^2}{(\sqrt3-1)(\sqrt3+1)}\\
\frac{x+3}{2x}=\frac{3+1+2\sqrt3}{3-1}\\
\frac{x+3}{2x}=\frac{2(2+\sqrt3)}{2}\\
\frac{x+3}{2x}=2+\sqrt3\\
x+3=x(4+2\sqrt3)\\
x(4+2\sqrt3-1)=3\\
x(3+2\sqrt3)=3\\
x=\frac{3}{3+2\sqrt3}\\
x=\frac{3(2\sqrt3 -3)}{(2\sqrt3+3)(2\sqrt3-3)}\\
[/tex]
[tex]x=\frac{3(2\sqrt3-3)}{12-9}\\
x=\frac{3(2\sqrt3-3)}{3}\\
x=2\sqrt3-3[/tex]